PEMBERDAYAAN BACILLUS THURINGIENSIS SEBAGAI BIOPESTISIDA PADA TANAMAN - Wiji Astuti, Wiwik; Hala, Yusminah (Jurnal Biogenerasi, 2024)
Plant pest control is a major challenge in the world of agriculture. The use of chemical pesticides that have been used so far leaves residues that have a negative impact on human health and environmental pollution. Biopesticides are present as a solution that can be used as an environmentally friendly pest control using natural ingredients such as microorganisms (bacteria, fungi), plant extracts and other natural ingredients. Bacillus thuringiensis (Bt) is a gram-positive bacteria that is widely used as a biopesticide to produce plant products that are resistant to pest attacks. The purpose of this study was to analyze the empowerment of Bacillus thuringiensis (Bt) as a biopesticide in plants. The method used is a literature study by reviewing information obtained from scientific articles, publication results and relevant research reports. The results of this study indicate that the Cry protein content in Bacillus thuringiensis (Bt) causes plants to be resistant to Lepidoptera insect pests.